THE ROLE OF THE CORNER OF LIVING NATURE IN NATURAL SCIENCE CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
A vibrant nature angle is used to create accurate and accurate perceptions of nature bodies and phenomena that cannot be directly accepted in children